Implementasi Pembelajaran Berbasis Proyek Terhadap Minat Belajar Siswa Di SMP Negeri 5 Katingan Tengah Dalam Mata Pelajaran IPA - yanti, Indri Dama; Setiawati, Nani; Yedithia, Fenroy (Journal Of Dehasen Educational Review, 2025)
This study aims to describe the implementation of project-based learning (PBL) on students' interest in learning science subjects at SMP Negeri 5 Katingan Tengah. The background of this study is based on the importance of developing contextual and innovative learning in accordance with the Merdeka Curriculum, which emphasizes student-centered learning through a project-based approach. The research method used is a qualitative approach with descriptive techniques. Data collection techniques included observation, interviews, and documentation, with the research subjects consisting of the school principal, science teachers, and 18 ninth-grade students. The results of the study indicate that the implementation of PBL has a positive impact on increasing students' interest in learning because the material taught is easier and quicker to understand. Students also become more active, creative, and engaged in the learning process. Additionally, PJBL encourages teachers to continue innovating in designing learning that is relevant to daily life. PJBL also enhances students' critical thinking, communication, collaboration, and responsibility skills when working in groups.